2008
DOI: 10.1115/1.2812968
|View full text |Cite
|
Sign up to set email alerts
|

Prestall Behavior of a Transonic Axial Compressor Stage via Time-Accurate Numerical Simulation

Abstract: Computational fluid dynamics calculations using high-performance parallel computing were conducted to simulate the prestall flow of a transonic compressor stage, NASA compressor Stage 35. The simulations were run with a full-annulus grid that models the 3D, viscous, unsteady blade row interaction without the need for an artificial inlet distortion to induce stall. The simulation demonstrates the development of the rotating stall from the growth of instabilities. Pressure rise performance and pressure traces ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…by some researchers for both low and high-speed compressors (e.g., [12][13] and [15]). In the recent experiments reported by Weichert and Day [9], however, no forward spillage was observed before and during the emergence of spike.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…by some researchers for both low and high-speed compressors (e.g., [12][13] and [15]). In the recent experiments reported by Weichert and Day [9], however, no forward spillage was observed before and during the emergence of spike.…”
mentioning
confidence: 99%
“…Therefore, as emphasized by in [9], "the debate about whether forward spillage occurs before or after stall onset is a topic of current interest which requires more numerical and experimental investigations". Some of the numerical studies reported on stall inception used part-span geometries to reduce the computational cost (e.g., [6][7][8] and [10]), whereas some others performed full-annulus computations (e.g., [11][12][13][14][15][16][17][18]). Hah et al [12] simulated spike-type stall inception in a transonic compressor rotor.…”
mentioning
confidence: 99%
“…In that case, numerical simulation can be an alternative and complementary way to experimental measurement in analysis of complex flow phenomena. During the past 15 years, Davis and Yao (2006), Chen et al (2008), Yao et al (2010) achieved some valuable results of the flow structure leading to stall by using computational fluid dynamics (CFD) methods.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the stall inception were always to find the initial moment and inception location as early as possible. The early structure of the stall inception was explained through measuring the static pressure at the initial moment of the stall (Inoue et al, 2000;Chen et al, 2007). The asymmetry of the structure caused the stall inception at the particular blade passage of an axial compressor (Weichert and Day, 2012).…”
Section: Detailed Measurements Of the Static Pressure Characteristicsmentioning
confidence: 99%